Kiswahili as a language for all Africa: The West Africa Challenge (Namibian Journal of Linguistics, Literature and Communication Studies, 2024)
The endorsement of Kiswahili as an official working language in AU meetings, conferences and communications gives Kiswahili a big boost. This comes in the midst of another milestone in which World Kiswahili day was set aside as July 7 by UNESCO. The AU did not only endorse Kiswahili as a language of official communication, it also added a resolution that by 2063, all African countries (member states) must have implemented full learning of Kiswahili language in an effort to have the language as the official language of Africa. The question then is, are all African countries ready for Kiswahili? Are there challenges that can be foreseen impeding the implementation of this policy? The paper investigates the challenges that may arise in making Kiswahili the language for Africa with specific reference to West Africa. The choice of West Africa is a purposive sampling methodological approach. The paper is guided by the socio-psychological theory which is one of the theories used in the study of second language learning. The outcome of this research will be essential in formulating the way forward in the implementation of the policy and designing strategies to make Kiswahili a working language for Africa with fewer challenges.
Keywords: AU; Second Language; Policy; Strategies; Kiswahili